Estimating Carbon Stock from Land Cover Dynamics Using Stock-Difference in Gunungpati - Andika Pangestu; Ananto Aji (Universitas Negeri Gorontalo, 2026)
Changes in land use in peri-urban areas directly affect vegetation structure and aboveground biomass carbon stocks, particularly in landscapes experiencing rapid settlement expansion. This study aimed to identify spatial and temporal patterns of land use change, estimate aboveground biomass carbon stocks for each land use class, and quantify the rate of carbon stock change in the Gunungpati District, Semarang City, from 2014 to 2024. Multi-temporal Landsat 8 imagery from 2014, 2019, and 2024 were classified into eight land use classes using supervised classification with the maximum likelihood algorithm. Carbon stocks were estimated by multiplying the area of each land use class by its carbon stock coefficient, while temporal carbon stock changes were quantified using the stock difference method. The results showed substantial land use transformation, marked by a sharp decrease in dryland agriculture, the dominance of mixed dryland agriculture, and continuous settlement expansion. Total carbon stock increased from 137,404.12 tons C in 2014 to 268,488.02 tons C in 2019, before declining to 240,020.17 tons C in 2024. The annual carbon-stock change was 26,216.78 tons C/year during 2014–2019, −5,693.57 tons C/year during 2019–2024, and 10,261.61 tons C/year during 2014–2024. These findings indicate that the Gunungpati District retained a net carbon stock gain over the study period; however, the post-2019 decline suggests increasing ecological pressure from settlement expansion. Protecting vegetation-based land covers is therefore essential to maintain the district’s role as a green open space reserve and to support climate change mitigation.